Mining for genes related to pistil abortion in Prunus sibirica L. - Jianhua Chen; Jian Zhang; Quangang Liu; Xinxin Wang; Jiaxing Wen; Yongqiang Sun; Shengjun Dong (PeerJ, 2022)
In Prunus sibirica, the phenomenon of pistil abortion is very common and seriously affects its fruit quality and yield; however, the molecular mechanisms of pistil abortion remains unclear. In this study, we identified differentially expressed genes (DEGs) and pathways associated with pistil abortion using transcriptome sequencing. After comparative analysis, a total of 1,950 DEGs were identified, of which 1,000 were upregulated, and 950 were downregulated. Gene Ontology (GO) functional enrichment analysis of DEGs showed that metabolic process, cellular process, single-organism process, membrane, membrane part, cell, binding, catalytic activity, and transporter activity contained the largest number of DEGs. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that the plant-pathogen interaction, starch and sucrose metabolism, and plant hormone signal transduction pathways contained the largest number of DEGs. The NAC, bHLH, and B3 transcription factor families contained the largest number of DEGs. qRT-PCR detection confirmed that the gene expression levels were consistent with the transcriptome sequencing results. This study provides a theoretical basis and scientific basis for further research on the molecular mechanisms of P. sibirica pistil abortion.